PEMUTUSAN HUBUNGAN KERJA AKIBATPEKERJA MELAKUKAN PELANGGARAN PERJANJIAN KERJA DI KOPERASI SAMUAN AMERTHA DENPASAR - Jiyestha Rika Putra, I Gede; Markeling, I Ketut; Dedy Priyanto, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013)
Denpasar is the provincial capital of Bali so the position is as a center of the economy. Various businesses including cooperatives are often found in the city of Denpasar and among these cooperatives is KoperasiSamuanAmertha Denpasar who was never a case of employment termination unilateral in the sense that the cooperative is to fire one of its employees without giving advance warning, and without giving severance pay for employees who are laid off. It is known by the data pre-study. There fore, I'm interested to write ajournal by lifting the title "Employment Termination Due to Breach Covenant Workers Doing Work In KoperasiSamuanAmertha Denpasar"
Keywords: Termination Of Employment, Labour, Violations, Employment Agreements